Pathogenic variants in BRCA1/2 genes among patients with triple-negative breast cancer: a case series - Costa, Rafael Everton Assunção Ribeiro da; Oliveira, Fergus Tomás Rocha de; Araújo, Ana Lúcia Nascimento; Vieira, Sabas Carlos (Mastology, 2021)
riple-negative breast cancer (TNBC) is an uncommon molecular subtype (representing 15%–20% of breast cancers) characterized by the non-expression of estrogen receptor, progesterone receptor, and human epidermal growth receptor factor 2. More aggressive and lethal, TNBC is often associated with pathogenic variants in BRCA1/2 genes. This study aimed to describe a series of seven cases of patients with TNBC and pathogenic variants in BRCA1/2 genes. All patients were female and under 50 years of age at diagnosis. Four of them presented a family history of breast cancer and/or other neoplasms. The predominant clinical stage was IIB, and the main anatomopathological stage was pT2pN0M0. The mean tumor size in the series was 2.5 cm (1.0 to 3.2 cm). Ki-67 was > 30% in all patients. Three cases (43%) had pathological complete response, and only one presented extensive residual disease after neoadjuvant chemotherapy. Six patients showed pathogenic variants in BRCA1 (86%) and one in BRCA2+ (14%). After a mean follow-up of 38 months (19 to 68 months), five patients were alive and without neoplastic disease, and two progressed to metastasis.